Entry and exit decisions in flexible teams - Christensen, Michael; Knudsen, Thorbjørn (Journal of International Business Studies, 2008)
The present study identifies a major limitation of current research on multinational enterprises (MNEs). Joint decision-making in a distributed setting is of critical importance in practice, but has received little attention in our theories. To address this gap in knowledge, we examine the effects of flexible decision teams when MNEs assess turbulent markets. Remarkably, flexible teams composed of fallible evaluators can outperform what is usually thought of as an “optimal” decision. Our main result supports the claims advanced in recent empirical studies. Structural flexibility can help MNEs achieve high levels of performance, even in conditions of turbulence.